2011
DOI: 10.3748/wjg.v17.i19.2411
|View full text |Cite
|
Sign up to set email alerts
|

Resected specimen evaluation, anorectal manometry, endoanal ultrasonography and clinical follow-up after STARR procedures

Abstract: The STARR procedure with two PPH-01 is a safe surgical procedure to correct ODS. The new Contour CCS 30 could help to increase the amount of the resected tissue without differences in early complications, post-operative pain and in hospital stay compared to the STARR with two PPH-01 technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 12 publications
2
3
0
2
Order By: Relevance
“…It is therefore not certain that the normal function is restored by correcting the anatomy. 21 Several studies have confirmed that the STARR procedure significantly improves constipation in most of the patients with ODS, as shown by the significantly improvement in scores of constipation after these procedure, 8,9 as confirmed by our results. Considering the correlation between postoperative satisfaction grading and postoperative constipation scores, it is interesting to note that only 57.1% of patients with poor satisfaction grading had poor scores as well.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It is therefore not certain that the normal function is restored by correcting the anatomy. 21 Several studies have confirmed that the STARR procedure significantly improves constipation in most of the patients with ODS, as shown by the significantly improvement in scores of constipation after these procedure, 8,9 as confirmed by our results. Considering the correlation between postoperative satisfaction grading and postoperative constipation scores, it is interesting to note that only 57.1% of patients with poor satisfaction grading had poor scores as well.…”
Section: Discussionsupporting
confidence: 86%
“…2,6,7 The STARR procedure could be performed by 2 PPH-01 stapling devices or a CCS-30 stapler (ETHICON Endosurgery, Cincinnati, OH), with the only difference of the amount of resected volume. In our experience 8 and in the current literature, a correlation between 505718S RIXXX10.1177/1553350613505718Surgical InnovationPanicucci et al research-article2013 1 University Hospital of Pisa, Pisa, Italy 2 University of Siena, Siena, Italy the amount of the prolapse removed and the functional improvement in patients with ODS has not been reported. 9,10 Several reports have shown that STARR significantly improves constipation in most patients, while others remain symptomatic for ODS.…”
Section: Introductionmentioning
confidence: 64%
“…Additionally, radiological and clinical modifications of intussusception and rectocele were observed in 94.6% of patients during the follow-up investigated by Arroyo et al[ 52 ]. Similar results were also reported by Ding et al[ 64 ] and Naldini et al[ 65 ]. Because a circular anal dilator (CAD) was introduced into the anus to provide a better view for surgeons, possible damage to anal sphincters due to the introduction of the CAD was considered by some investigators.…”
Section: Alternative Transanal Surgical Procedures For Odssupporting
confidence: 92%
“…However, there were also some opposing views. Wadhawan et al[ 97 ] and Naldini et al[ 65 ] indicated that there were no statistically significant differences in postoperative clinical outcome, early complications, postoperative pain or hospital stay between PPH-STARR procedure and Contour-Transtar procedure. Similarly, Boccasanta et al[ 98 ] demonstrated that no improvements in symptoms and defecographic parameters were observed postoperatively in patients who underwent operation using Contour-Transtar procedure compared with PPH-STARR procedure.…”
Section: Alternative Transanal Surgical Procedures For Odsmentioning
confidence: 99%
“…In the other two RCTs of lesser quality (IIB), STARR (PPH01) was shown to be significantly better for functional outcome compared with biofeedback (although there was > 50% attrition rate in the biofeedback group) [21], and STARR (PPH01) was shown to give similar functional results compared with Intra-anal Delorme's with levatoroplasty [57]. In other non-randomised (level IIB) comparisons of STARR (PPH01) vs Contour Transtar [8,27,43] there was no difference in functional outcome. One prospective cohort study (level IIB) compared PPH01 with PPH03 [18] and showed no difference in functional outcome, and a further compared STARR with macrogol therapy [8].…”
Section: Efficacymentioning
confidence: 99%